2017
DOI: 10.1107/s1600576717002977
|View full text |Cite
|
Sign up to set email alerts
|

Observation of sagittal X-ray diffraction by surface acoustic waves in Bragg geometry

Abstract: X-ray Bragg diffraction in sagittal geometry on a Y-cut langasite crystal (La3Ga5SiO14) modulated by Λ = 3 µm Rayleigh surface acoustic waves was studied at the BESSY II synchrotron radiation facility. Owing to the crystal lattice modulation by the surface acoustic wave diffraction, satellites appear. Their intensity and angular separation depend on the amplitude and wavelength of the ultrasonic superlattice. Experimental results are compared with the corresponding theoretical model that exploits the kinematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…CRLs enable the observation of diffraction satellites in the focal plane. It was shown by Vadilonga, Zizak, Roshchupkin, Evgenii et al (2017) that diffraction orders can be observed at large distances with a CCD camera if use is made of short-wavelength SAWs. In our case, a SAW wavelength of à = 3 mm and a distance of 120 cm after the acoustically modulated crystal enabled the observation of diffraction orders and examination of the dependence of their intensities on the amplitude of the input signal on the IDT in the range U = 0-20 V. Fig.…”
Section: X-ray Bragg Diffraction By Acoustically Modulated Crystals Imentioning
confidence: 99%
“…CRLs enable the observation of diffraction satellites in the focal plane. It was shown by Vadilonga, Zizak, Roshchupkin, Evgenii et al (2017) that diffraction orders can be observed at large distances with a CCD camera if use is made of short-wavelength SAWs. In our case, a SAW wavelength of à = 3 mm and a distance of 120 cm after the acoustically modulated crystal enabled the observation of diffraction orders and examination of the dependence of their intensities on the amplitude of the input signal on the IDT in the range U = 0-20 V. Fig.…”
Section: X-ray Bragg Diffraction By Acoustically Modulated Crystals Imentioning
confidence: 99%
“…Different X-ray diffraction schemes are used for nondestructive experimental studies of crystals modulated by a SAW, including traditional double- (Roshchupkin et al, 2003) and triple-axis (Punegov et al, 2010) diffractometry. Recently, diffraction schemes in the sagittal Bragg geometry (Vadilonga et al, 2017), as well as schemes using the coherent diffraction of a time-resolved nanofocus synchrotron beam (Reusch et al, 2013;Nicolas et al, 2014) and with composite parabolic lenses (Roshchupkin et al, 2011), have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser beam is introduced into the beamline before the sample chamber, and can be focussed to the same spot at the sample. Di erent X-ray detectors are mounted outside of the vacuum and can be rotated up to scattering angle of 90 • (Helmholtz-Zentrum Berlin für Materialien und Energie, 2016; Iurchuk et al, 2016;Navirian et al, 2014;Roshchupkin et al, 2016;Vadilonga et al, 2017).…”
Section: Instrument Applicationmentioning
confidence: 99%